A Study on English Department Students' Reading Strategies at English Department UNP - Elvi Susanti; Fitrawati Fitrawati (Journal of English Language Teaching, 2020)
Reading is not just a source of information and exciting experiences, it is also a key part of language training at all stages, as it facilitates various ways of learning. Reading strategies are one of method to help students in improving their reading ability and make easier in grasp the meaning of the text.  This study aimed to investigate the reading strategies used by English Department Students in tertiary level at Universitas Negeri Padang. Specifically, it focused to identify the reading strategies frequently used by the students. Sixty-three undergraduate students were randomly selected as the respondents for this study, a fifty-item questionnaire which focused on the frequency of use of pre, while, and post-reading strategies was applied in the study. In addition, the researcher used interview method according to ten-high score based on questionnaire result to delved students’ reading strategies in reading phases. English Students at UNP were observed have been found to typically re-check readings or phrases that were not known during the reading process.